The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/inf.0000000000001400
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease in Children in Tonga

Abstract: In Tonga, pneumococcal conjugate vaccine is not a scheduled immunization. We identified all children in Tonga with invasive pneumococcal disease from 2010 to 2013. The average annual invasive pneumococcal disease incidence rate was 113/100,000 (<2 years), 50/100,000 (<5 years) and 25/100,000 (<15 years). The case fatality rate (<5 years) was 25%. The incidence rate and high case fatality rate indicate the need for pneumococcal conjugate vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…This could be mainly seen in the suburban areas in the country. The findings are complying with the study conducted by Lutui (2001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This could be mainly seen in the suburban areas in the country. The findings are complying with the study conducted by Lutui (2001).…”
Section: Discussionsupporting
confidence: 88%
“…The Cronbach's alpha obtained with the present sample was 0.637. The conceptual framework was developed based on the previous research work conducted by (Lutui, 2001) and adapted accordingly to suit Sri Lankan Context. Methods used to analyse data were Cross tab and Statistical package for social sciences (SPSS) Version 20.0 was used to analyse data.…”
Section: Methodsmentioning
confidence: 99%
“…Invasive pneumococcal disease was defined as isolation of S. pneumoniae in a sterile fluid such as blood, cerebrospinal (CSF), pleural or joint fluids 18,26,27 .…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…A literature review found seven papers investigating PCV in Pacific Island nations, with 5 from Fiji [ 7 - 11 ], one from Papua New Guinea [ 12 ], and another from Tonga [ 13 ]. Three of the papers from Fiji evaluated the effect of 10-valent PCV introduction in October 2012 and found that results were overall very positive.…”
Section: Pcv and The Prevention Of Otitis Media And Hearing Loss Amon...mentioning
confidence: 99%
“…The study from Tonga aimed to evaluate hospital admissions of invasive pneumococcal disease in a nation that has no pneumococcal vaccine program [ 13 ]. The calculated incidence rates were 113/100 000 for children under 2 years, 50/100 000 for children under 5 years, and 25/100 000 for children under 15 years.…”
Section: Pcv and The Prevention Of Otitis Media And Hearing Loss Amon...mentioning
confidence: 99%